Growth and Luminescence of Polytypic InP on Epitaxial Graphene. (20th December 2017) - Mukherjee, Samik; Nateghi, Nima; Jacobberger, Robert M.; Bouthillier, Etienne; de la Mata, Maria; Arbiol, Jordi; Coenen, Toon; Cardinal, Dhan; Levesque, Pierre; Desjardins, Patrick; Martel, Richard; Arnold, Micheal S.; et al.
Abstract: Van der Waals epitaxy is an attractive alternative to direct heteroepitaxy where the forced coherency at the interface cannot sustain large differences in lattice parameters and thermal expansion coefficients between the substrate and the epilayer. Herein, the growth of monocrystalline InP on Ge and SiO2 /Si substrates using graphene as an interfacial layer is demonstrated. Micrometer‐sized InP crystals are found to grow with interfaces of high crystalline quality and with different degrees of coalescence depending on the growth conditions. Some InP crystals exhibit a polytypic structure, consisting of alternating zinc‐blende and wurtzite phases, forming a type‐II homojunction with well (barrier) width of about 10 nm. The optical properties, investigated using room temperature nano‐cathodoluminescence, indicate the signatures of the direct optical transitions at 1.34 eV across the gap of the zinc‐blende phase and the indirect transitions at≈ 1.31 eV originating from the alternating zinc‐blende and wurtzite phases. Additionally, the InP nanorods, found growing mainly on the graphene/SiO2 /Si substrate, show optical transition across the gap of the wurtzite phase at≈ 1.42 eV. This demonstration of InP growth on graphene and the correlative study between the structure and optical properties pave the way to develop hybrid structures for potential applications in integrated photonic and optoelectronic devices. Abstract : The InP–graphene hybrid structures achieved by exploiting quasi van der Waals epitaxy on group IV substrates are illustrated. The room temperature optical emissions the signature transitions across the zinc‐blend gap as well as alternating zinc‐blende/wurtzite phases, forming a type II homojunction. The development of these hybrid structures lays the groundwork to implement innovative photonic and optoelectronic devices.